Influence of fuel bio-alcohol content on the performance of a turbo-charged, PFI, spark-ignition engine. (1st March 2019) - Galloni, E.; Scala, F.; Fontana, G.
Abstract: In this work, the behavior of an engine running with binary and ternary mixtures of n-butanol, ethanol and gasoline has been investigated. Analyses have been performed at different engine speed both at low load and at high load. For each blend, the air to fuel ratio has been kept stoichiometric, while the spark time has been tuned in order to maximize the engine brake torque and hence the engine fuel conversion efficiency. The performance, the combustion characteristics and the pollutant emissions of the engine fueled by biofuel mixtures have been compared to those characterizing the engine running with neat gasoline. In an attempt to provide a guideline for the development of engines running with every mix of gasoline and alcohol, measurements are presented as a function of the oxygen content of the fuel. When the fuel oxygen content increases, results show that the optimal spark time must be retarded at part load while must be advanced at high load. At this operation, the maximum obtainable efficiency increases, the CO2 specific emissions decrease almost linearly together with NOx and HC specific emissions, the engine torque remains practically the same, while the brake specific fuel consumption increases. Graphical abstract: An engine running with alcohol-gasoline blends has been investigated. Analyses have been performed at different engine speed both at low load and at high load. The air to fuel ratio has been kept stoichiometric. When the alcohol content increases, results show that the optimal spark time must be retarded at part load while must be advanced at high load. At this operation, the maximum obtainable efficiency increases and the CO2 specific emissions decrease. The engine torque remains practically the same, while the brake specific fuel consumption increases. Trends are almost linearly with respect to the fuel oxygen content.Image 105 Highlights: A spark ignition engine running with alcohol/gasoline blends has been investigated. When the alcohol content increases: the maximum obtainable engine efficiency increases. the spark timing must be retarded at part load and advanced at high load. specific CO2 emissions decrease. A guideline for tuning of engines burning alcohol-gasoline blend has been obtained.